2015
DOI: 10.3758/s13423-015-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell-phone use diminishes self-awareness of impaired driving

Abstract: Multitasking diminishes the self-awareness of performance that is often essential for self-regulation and selfknowledge. Participants drove in a simulator while either talking or not talking on a hands-free cell phone. Following previous research, participants who talked on a cell phone made more serious driving errors than control participants who did not use a phone while driving. Control participants' assessments of the safeness of their driving and general ability to drive safely while distracted were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…of the V. ISHE Summer Institute(2018): 48-57 distractions from multitasking (Lipovac et al, 2017). Participants in a driving simulator made more serious driving errors when using a cell phone than when not using a cell phone (Sanbonmatsu et al, 2016). Cell phone using participants did not remember making a greater number of serious errors and were less accurate in their estimates of their error rates than non-cell phone using participants (Sanbonmatsu et al, 2016).…”
Section: Driving Distraction From Cell Phone Usementioning
confidence: 94%
See 1 more Smart Citation
“…of the V. ISHE Summer Institute(2018): 48-57 distractions from multitasking (Lipovac et al, 2017). Participants in a driving simulator made more serious driving errors when using a cell phone than when not using a cell phone (Sanbonmatsu et al, 2016). Cell phone using participants did not remember making a greater number of serious errors and were less accurate in their estimates of their error rates than non-cell phone using participants (Sanbonmatsu et al, 2016).…”
Section: Driving Distraction From Cell Phone Usementioning
confidence: 94%
“…Participants in a driving simulator made more serious driving errors when using a cell phone than when not using a cell phone (Sanbonmatsu et al, 2016). Cell phone using participants did not remember making a greater number of serious errors and were less accurate in their estimates of their error rates than non-cell phone using participants (Sanbonmatsu et al, 2016). Driving simulations indicate that using a phone while driving produces reaction time delays equivalent to having the legal limit of alcohol intoxication in most US states (Strayer et al, 2006).…”
Section: Driving Distraction From Cell Phone Usementioning
confidence: 99%
“…For instance, talking on a mobile phone while driving dramatically increases the likelihood of making dangerous driving errors (Sanbonmatsu, Strayer, Biondi, Behrends, & Moore, 2016), with driving performance affected as much as when drivers are legally drunk (Strayer, Drews, & Crouch, 2006). In addition, driving while using a mobile phone also decreases accuracy of perceptions about driving safety (Sanbonmatsu et al, 2016). People even walk differently while using mobile phones, with behavior that indicates an attentional blindness to surroundings (Hyman, Boss, Wise, McKenzie, & Caggiano, 2010).…”
Section: Potential Challenges Of An Emi Supplement To a Mindfulness Imentioning
confidence: 99%
“…This overinflated belief in driving ability can lead to greater engagement in dangerous driving behaviours such as mobile phone use (Hill et al, 2014). A recent simulator study of undergraduate students in an American university (Mage = 21.8 years) found that there was no correlation between self-assessment of driving safeness and actual driving errors (Sanbonmatsu, Strayer, Biondi, Behrends, & Moore, 2015). The authors concluded that not only did mobile phone use reduce the safeness of their participants' driving but it also impaired their awareness of their safeness.…”
Section: Critical Belief Possible Message Content and Strategiesmentioning
confidence: 99%
“…The authors concluded that not only did mobile phone use reduce the safeness of their participants' driving but it also impaired their awareness of their safeness. As a result, young drivers will continue to use their mobile phones while driving as long as they believe they can safely do so (Sanbonmatsu et al, 2015). Young drivers need to be challenged and presented with the reality that they are only good drivers when they are not using their smartphone.…”
Section: Critical Belief Possible Message Content and Strategiesmentioning
confidence: 99%